Prevalence of Diseases and Observation of Drug Utilization Pattern in Geriatric Patients: A Home Medication Review - Awanish, Pandey; Poonam, Tripathi; Rishabh Dev, Pandey (Indian Journal of Pharmacy Practice)
Geriatric patients may have medication-related risk factors only identified by home visits, but the extent to which thoserisk factors are associated with poor health outcomes remainsunclear. To observe the drug utilization pattern and prevalence of chronic diseases in elderly by visiting them in their community. A door-to-door survey was conducted in an area of 2 sq. km surrounding Shri Mahant Indiresh Hospital of Dehradun, to identify geriatric residents, diseases prevalent in them and prescription pattern. The study was primarily targeted at the elderly because, as a group they take more drugs than their younger counterparts and are known to be at risk of the side effects of many of the drugs they consume. The result of this study showed that 34 % geriatric patients were suffering from cardiac disorder while 22% from diabetes and 18% from osteoarthritis among elderly population. 40% patients were non-compliant due to poor economic status, difficulty in swallowing of the prescribed dosage forms, and disturbing side effects. Self-medication (38%) was a prevalent phenomenon among the elderly. The study conclude that cardiac disorders, diabetes and rheumatism were the most prevalent diseases and self-medication was the prevalent phenomenon responsible for the adverse drug reactions in geriatric patients. The study suggests that elderly patient education through home medication review can significantly improve patient knowledge and compliance with medication.
Keywords: Home medication review; Noncompliance; Selfmedication; Geriatrics; Polypharmacy